Microscopic Positive Tumor Margin Increases Risk for Disease Persistence but Not Recurrence in Patients with Stage T1-T2 Differentiated Thyroid Cancer. (10th January 2020) - Kamel Hasan, Olfat; De Brabandere, Sarah; Rachinsky, Irina; Laidley, David; MacNeil, Danielle; Van Uum, Stan
Abstract : Introduction . Differentiated thyroid cancer (DTC) has an overall excellent prognosis. Patients who develop recurrent disease have a more unfavorable disease course than those with no recurrence. Higher recurrence rates are seen with incomplete surgical resection and gross positive margins. It is unclear whether microscopic positive margin affects disease recurrence rates as much as grossly positive margin. Aim of the Study . To assess whether microscopic positive margin is an independent predictor of disease recurrence in patients with overall low-risk DTC. Patients and Methods . We conducted a retrospective single-center institutional review of 1, 583 consecutive patients' charts from 1995–2013 using the Canadian Thyroid Cancer Consortium Registry. We included adult patients with nonmetastasizing T1 and T2 DTC with a minimum of three years follow-up. Univariate and multivariate analyses were used to study factors that may influence the risk of persistent/recurrent disease. Strict definitions of persistent versus recurrent disease were applied. Results . 963 patients (152 men and 811 women) were included in the study with a mean age of 46 years. Microscopic positive margins were present in 12% of the specimens and were associated with an increased rate of persistent disease (8% versus 2% in the controls) but not with an increased risk of recurrent disease (1% in both groups). T2 tumors had a significantly higher incidence of positive margins than T1 tumors (48% versus 36%) and significantly higher nodal staging. Conclusions . Microscopic positive margin in the histopathology report in patients with low-risk DTC was associated with a higher rate of persistent disease but did not increase the risk of disease recurrence. A close follow-up of biomarkers and occult residual cancerous lesions is needed, especially in the first year. Further studies are needed to determine whether additional therapeutic measures to prevent recurrence are indicated in T1 and T2 DTC with positive microscopic surgical margins.